2019
DOI: 10.1111/cbdd.13473
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophoric features for a very potent 5‐spirofluorenehydantoin inhibitor of cancer efflux pump ABCB1, based on X‐ray analysis

Abstract: In order to extend knowledge about pharmacophoric features responsible for ABCB1 inhibitory properties of imidazolidin‐2,4‐dione derivatives, 1′‐[4‐(4‐(o‐methoxyphenyl)‐piperazin‐1‐yl)butyl]‐3′‐methyl‐spiro(fluoren‐9,5′‐imidazolidine)‐2′,4′‐dione (3) and its salt (4) with rhodanine‐3‐acetic acid (RA) were prepared and investigated by X‐ray diffraction method, as well as their efflux modulating effects in cancer cells (mouse T‐lymphoma), cytotoxic and antiproliferative activities were evaluated in vitro. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The angle between the corresponding planes amounts to 88.26(5)°. This arrangement is similar to other 5-spirofluorenehydantoin derivatives with determined crystal structures [32,33,37,38]. The linker between the hydantoin and piperazine rings, consisting of four methylene moieties, is flexible.…”
Section: Crystallographic Studiessupporting
confidence: 76%
“…The angle between the corresponding planes amounts to 88.26(5)°. This arrangement is similar to other 5-spirofluorenehydantoin derivatives with determined crystal structures [32,33,37,38]. The linker between the hydantoin and piperazine rings, consisting of four methylene moieties, is flexible.…”
Section: Crystallographic Studiessupporting
confidence: 76%
“…In our previous studies we have explored the importance of a basic BPA skeleton 48 , and concluded that BPA could serve as a “pharmacophore”, necessary to retain anti-glioblastoma activity 49 , 50 . The amide part of the BPA skeleton can be specifically modelled to obtain a more desirable anti-tumor activity.…”
Section: Resultsmentioning
confidence: 99%
“…Overall Chemical Design: In our previous studies we have explored the importance of a basic BPA skeleton 31 , and concluded that BPA could serve as a "pharmacophore", necessary to retain anti-glioblastoma activity 32,33 . The amide part of the BPA skeleton can be specifically modelled to obtain a more desirable anti-tumor activity.…”
Section: Results and Discussonmentioning
confidence: 99%